If 7 x + 7 = 8 x , x = lo g b 7 7 and b = n m . Find m + n
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If x = logb(7^7), so b^x = 7^7 . Then, b = 8/7
Log in to reply
Fail to see how b = 7 8 f r o m b x = 7 7
7 x + 7 = 8 x
lo g 7 x + 7 = lo g 8 x
( x + 7 ) lo g 7 = x lo g 8
x ( lo g 8 − l o g 7 ) = lo g 7 7
x = lo g 8 − lo g 7 lo g 7 7 = lo g 7 8 lo g 7 7
Apply change of base:
x = lo g 7 8 1 0 lo g 7 8 7 8 lo g 7 8 1 0 lo g 7 8 7 7 = lo g 7 8 7 7
∴ b = 7 8 and m + n = 1 5
this solution is way more accessible than the first one. however, the changing of base is an unnecessary step because your initial logarithm log7^(x+7) has the base 10 as well as log8^x therefore the fraction where you get to x is between 2 logarithms with the same base (10) and the formula is just what you got by changing the base. all in all, good solution and simpler.
i cant understand the fourth step
(7^7)(7^x) = 8^x
7^7 = (8/7)^x
Taking the logarithm for the base b
log (7^7) = x log (8/7) = x
Then
log (8/7) = 1
Then
b = 8/7 = m/n
Then
m + n = 8 + 7 = 15
7^(x + 7) = 8^x (x + 7)ln(7) = xln(8) x = 7ln(7)/(ln(8/7)) = 7*log(base 8/7) 7 Therefore b = 8/7 m + n = 15 OR
Simply from 1st equation, we get
7^7 = (8/7)^x
Substituting the value of 7^7 in 2nd equation, we get
x = log b (8/7)^x where b is the base of the log
Thus,
x = x log b (8/7)
Thus, we get
b = 8/7 = m/n
Therefore, m = 8 and n = 7
So, m+n = 15
Since, x = lo g b 7 7 , therefore, b x = 7 7 → ( 1 ) , it is also apparent that b > 0 .
Then,
Since, 7 x + 7 = 8 x , therefore 7 x ⋅ 7 7 = 8 x , then substituting from ( 1 ) , therefore, 7 x ⋅ b x = 8 x .
Now taking x t h root of both sides ,
Therefore, x 7 x ⋅ b x = x 8 x ,
Then , 7 ⋅ b = 8 ,
Therefore, b = 7 8 = n m ,
Therefore, m + n = 8 + 7 = 1 5 .
Problem Loading...
Note Loading...
Set Loading...
7 x + 7 = 7 x ∗ 7 7 = 8 x ∴ 7 7 = ( 7 8 ) x x = lo g b 7 7 = lo g b ( 7 8 ) x = x ∗ lo g b ( 7 8 ) ⟹ 1 = lo g b ( 7 8 ) ⟹ b 1 = 7 8 m + n = 1 5